INFLUENCE OF IRRIGATION REGIMES AND FERTIGATION LEVELS ON YIELD AND PHYSIOLOGICAL PARAMETERS IN CAULIFLOWER - S. D. YANGLEM,; A. D. TUMBARE, (The Bioscan, 2014)
Scheduling of irrigation at 1.2 ETc irrigation regimes recorded significantly maximum curd yield (37.58 t ha-1) than 0.6, 0.8 and 1.0 ETc irrigation regimes. The higher fertigation level i.e., 100 per cent RD of N and K at every week up to 60 DAT and phosphorus as basal dose registered maximum curd yield (38.94 q ha-1). The Maximum photosynthetic rate, stomatal conductance and transpiration rate and minimum leaf temperature and stomatal resistance were observed due to 1.2 ETc irrigation regimes and 100 % RDF at all crop growth stages of cauliflower. The positive and highly significant correlation was observed between growth and yield attributes and physiological parameters (photosynthetic rate, stomatal conductance and transpiration rate) whereas negative correlation was observed with leaf temperature and stomatal resistance at all the growth period.